2023
DOI: 10.1108/jiabr-12-2021-0324
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the linkage between Islamic financial literacy and Islamic banking services adoption: evidence from Turkey

Abstract: Purpose The purpose of this study is twofold. First, this research explores the level of Islamic financial literacy of customers in the context of Islamic banking. Second, this study examines the determinants of customer adoption of Islamic banking in Turkey. Design/methodology/approach This study gathered sample data from 409 participants determined using the purposive sampling method. In the study, first, the reflective measurement model is used to examine the reliability, validity and multicollinearity pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…According to Roemanasari et al, (2022), financial literacy can be seen from knowledge related to financial management in general, the prohibition of usury transactions, contracts in Islamic finance, and Islamic financial products. Research by Pala et al (2023) states that Islamic financial literacy has a significant and positive impact on decisions. The technology used in Islamic finance will increase along with Islamic financial literacy.…”
Section: Perceived Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Roemanasari et al, (2022), financial literacy can be seen from knowledge related to financial management in general, the prohibition of usury transactions, contracts in Islamic finance, and Islamic financial products. Research by Pala et al (2023) states that Islamic financial literacy has a significant and positive impact on decisions. The technology used in Islamic finance will increase along with Islamic financial literacy.…”
Section: Perceived Riskmentioning
confidence: 99%
“…Elhajjar & Ouaida (2019) indicated that perceived risk has a positive and significant effect on decisions, but Purnamasari et al 's research (2021) showed that perceived risk has a negative and insignificant impact on decisions. Pala et al, (2023) stated that Islamic financial literacy has a positive and significant impact on decisions, but Mas'ud & Amang (2023) indicated that Islamic financial literacy has a negative and insignificant impact on decisions.…”
Section: Introductionmentioning
confidence: 99%